Fast Fashion Consumption Behavior According to Islamic Consumption Ethics and Sustainability - Ighfirly Hariroh; Naili Jazilinni’am; Irham Zaki (Jurnal Informatika Ekonomi Bisnis, 2026)
This article discusses the growing phenomenon of fast fashion and how people's consumption patterns of fast fashion products are viewed from the perspective of Islamic consumption ethics and environmental sustainability. Fast fashion is often criticized for its impact on the environment and labor exploitation. In Islam, consumption should be balanced, not excessive, and should prioritize sustainability. This research is quantitative with an explanatory approach, aiming to explain the causal relationship between the variables studied. The type of data used in this study is primary data, in the form of information obtained directly from respondents through questionnaires. This article discusses the growing phenomenon of fast fashion and how people's consumption patterns of fast fashion products are reviewed from the perspective of Islamic consumption ethics and environmental sustainability. Fast fashion is often criticized for its impact on the environment and labor exploitation. In Islam, consumption should be balanced, not excessive, and pay attention to sustainability aspects. This research is quantitative with an explanatory approach, aiming to explain the causal relationship between the variables studied. The type of data used in this study is primary data in the form of information obtained directly from respondents through questionnaires.